ACHIEVING A CORRUPTION-FREE SYSTEM BY SUPPORTING THE IMPLEMENTATION OF THE GENDER EQUALITY STRATEGY IN CUSTOMS AUTHORITIES (American Journal of Interdisciplinary Research and Development, 2024)
In this article, an honorable and hard-working customs official who contributes to the promotion of the future of Uzbekistan by supporting the strategy of gender equality and preventing corruption in the bodies of the Customs Committee under the Ministry of Economy and Finance of the Republic of Uzbekistan Uzbek women and the UN Development Program "Gender Equality Badge of State Institutions" program were widely covered.